A review of collaborative commerce business based on enterprise application integration in Vietnam - Vo, K. Q. (Indian Society for Education and Environment, 2016)
The systems in enterprises are often disjointed together and not interchangeable. Enterprise Application Integration (EAI) is essential to accommodate new business needs in the short- to moderate-term future by providing a right architecture. EAI has helped system to integrate various sources including plug-and-play interoperability. With the pressure in the business environment of information technology field, a demand for financial and security is getting drastically high which enforces the enterprises to learn how to use the existing database and services, reinvent business processes and databases. The objective of this paper is to provide an overview of collaborative commerce business in Vietnam that based on EAI as a solution to the demand. The outcome of this paper reveals that to have an effective integration, applications in enterprises need to be merged in terms of platform, data format, protocol and EAI technologies.